Konsep Pendidikan KH. Ahmad Sanusi - Handoko, Hanwar Priyo (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2016)
The effort of Ahmad Sanusi to develop in education through Ibtidaiyah educational board and Madrsah Diniyah to teach religion aspect and general knowledge that based on Islamic rule. To increase and develop the knowledge of Kyai its makes leadership training, general knowledge training, religion, politic, and then active in weekend discussion as a way to discuss and increase in religion knowledge. The level of education in the college consists of three levels: low level, middle level, and high level. Every level consists of four classes, such as: class I to class IV in four month. The curriculum that made and aplicated in Pesantren concern in religion aspect: Tafsir (translating), and nahwu sorof, otherwise the method that use the Sorogan method that combinating with discussion.